(untitled) (Journal of Bio-Science, 2023)
A suitable micropropagation protocol and ex vitro acclimation method have been developed from in vitro grown seedling explants through cotyledonary node and leaf explants in consideration of the vegetable and medicinal properties of Greater Burdock. MS medium with 0.5-4.0 μM BAP showed highest percentage of axillary shoot regeneration from the cotyledonary nodal explants. Direct shoot regeneration was achieved by culturing 1.0 cm2 sections of about 25 days old leaves of in vitro grown shoot on MS medium enriched with 4.0 μM BAP and 2.0 μM IBA or NAA after 5 weeks of culture. Within six weeks of incubation on medium enriched with 4.0 M BAP and 2.0 M IBA or NAA, the leaf explants also developed callus from the cut margins. The greatest number of adventitious shoots could then be formed from the leaf-derived callus within 10 weeks of culture on the same media mix. More than 20 shoots were formed per callus clump at the third subculture, which had the highest rate of shoot multiplication. A. lappa’s shoot and callus were both preserved at 5 ºC in MS medium with 4.0 μM Kn and 2.0 μM IBA, as well as 4.0 μM BAP and 2.0 μM IBA, respectively. The in vitro proliferated and elongated shoots were separated from callus clump for rooting. A root-induction MS medium with 6.0 μM IBA or NAA was used to cultivate the microshoots individually. All of the cultured microshoots generated 2-16 roots within 4 weeks of being moved to the rooting medium. Regenerated plantlets were transferred to vermiculite and successfully established in an ex vivo environment with a 98% survival rate. J. Bio-Sci. 31(1): 1-15, 2023